Bringing down the iron curtain : paradigmatic change in research on the Bronze Age in Central and Eastern Europe? - Šabatová, Klara; Dietrich, Laura; Dietrich, Oliver; Harding, A. F.; Kiss, Viktória, 1972- (Archaeopress Archaeology, 2020)
Bringing down the Iron Curtain: Paradigmatic changes in research on the Bronze Age in Central and Eastern Europe? presents the researches of scholars of different generations from twelve countries (Hungary, Romania, Czech Republic, Slovakia, Serbia, Croatia, Ukraine, United Kingdom, Germany, USA, Canada, Austria) who participated in a session of the same title at the 20th Meeting of the European Association of Archaeologists in Istanbul, 2014. The papers addressed the question of change in the approaches to Bronze Age research in the Central and Eastern European countries from different points of view.